Time in exile in conversation with Heidegger, Blanchot, and Lispector - Schuback, Marcia Sá Cavalcante (Intersections (Albany, N.Y.), 2020)
"This book is a philosophical reflection on the experience of time from within exile. Its focus on temporality is unique, as most literature on exile focuses on the experience of space, as exile involves dislocation, and moods of nostalgia and utopia. Marcia Sá Cavalcante Schuback proposes that in exile, time is experienced neither as longing back to the lost past nor as wanting a future to come but rather as a present without anchors or supports. She articulates this present as a "gerundive" mode, in which the one who is in exile discovers herself simply being, exposed to the uncanny experience of having lost the past and not having a future. To investigate this, the book establishes a conversation among three authors whose work has exemplified this sense of gerundive time: the German philosopher Martin Heidegger, the French writer and essayist Maurice Blanchot, and the Brazilian writer Clarice Lispector. The book does not aim to discuss how these authors understand the relation between time and exile but enters in conversation with them in relation to this question. Attempting to think and express this difficult sense of time from within exile, the book engages with the relation between thought and language, and between philosophy and literature. Departing from concrete existential questions, it opens new philosophical and theoretical modes through which to understand what it means to be present in times of exile"--